Chiral resolution of serial potent and selective σ1 ligands and biological evaluation of (−)-[18F]TZ3108 in rodent and the nonhuman primate brain. Issue 4 (15th February 2017) - Yue, Xuyi; Jin, Hongjun; Luo, Zonghua; Liu, Hui; Zhang, Xiang; McSpadden, Ethan D.; Tian, Linlin; Flores, Hubert P.; Perlmutter, Joel S.; Parsons, Stanley M.; Tu, Zhude
Graphical abstract: Abstract: Twelve optically pure enantiomers were obtained using either crystallization or chiral high performance liquid chromatography (HPLC) separation methodologies to resolve six racemic sigma-1 ( σ 1 ) receptor ligands. The in vitro binding affinities of each enantiomer for σ 1, σ 2 receptors and vesicular acetylcholine transporter (VAChT) were determined. Out of the 12 optically pure enantiomers, five displayed very high affinities for σ 1 (Ki < 2 nM) and high selectivity for σ 1 versus σ 2 and VAChT (>100-fold). The minus enantiomer, (−)-14a ((−)-TZ3108 ) (Ki- σ 1 = 1.8 ± 0.4 nM, Ki- σ 2 = 6960 ± 810 nM, Ki-VAChT = 980 ± 87 nM), was chosen for radiolabeling and further in vivo evaluation in rodents and nonhuman primates (NHPs). A biodistribution study in Sprague Dawley rats showed brain uptake (%ID/gram) of (−)-[ 18 F]TZ3108 reached 1.285 ± 0.062 at 5 min and 0.802 ± 0.129 at 120 min. NHP microPET imaging studies revealed higher brain uptake of (−)-[ 18 F]TZ3108 and more favorable pharmacokinetics compared to its racemic counterpart. Pretreatment of the animal using two structurally different σ 1 ligands significantly decreased accumulation of (−)-[ 18 F]TZ3108 in the brain. Together, our in vivo evaluation results suggest that (−)-[ 18 F]TZ3108 is a promising positron emission tomography (PET) tracer for quantifying σ 1 receptor in the brain.